Функциональный закон повторного логарифма для полей и его применения - Бондарев, Б.В.; Жирный, Г.Г. (Український математичний журнал, 1997)
Для вінерівського поля з довільним скінченним числом параметрів побудовано закон повторного логарифма у функціональному вигляді. Розглянуто задачу про перебування випадкових полів одного типу в криволінійних межах. Виконання умови Каіролі-Уолша не вимагається. For a Wiener field with an arbitrary finite number of parameters, we construct the law of the iterated logarithm in the functional form. We consider the problem for random fields of a certain type to reside within curvilinear boundaries without assuming that the Cairoli—Walsh condition is satisfied.